The Practicality of Learning Devices Cooperative Models Based on Blended Learning to Improve Learning Outcomes of 10th-Grade MA Students - Al Husaini; Hendra Syarifuddin; Usmadi Usmadi (International Journal of Trends in Mathematics Education Research, 2019)
Less active and low learning outcomes of students learning by the learning model used by the teacher. Among the variations that can be done is to take advantage of existing technological developments. Therefore, a study was conducted involving the development of learning devices. The research carried out was the development of cooperative learning mathematical learning tools in the form of Blended Learning Based Student Worksheets (LKPD). This study aims to produce a blended learning based learning tool that is practical to improve student learning outcomes. This development research uses the Plomp model which consists of three phases namely the initial investigation phase, the development phase, and the improvement phase. The subjects of this study were 10th-grade religion students of MA KMM Kauman Padangpanjang. Based on the learning outcomes, students are active in learning. The results of the interview show that the devices are easily developed and motivate students in learning and the results of the practicality questionnaire that shows the learning tools developed have met the practical requirements in terms of implementation, ease and time needed. The value of each meeting also increases with an average value of 83 daily test scores. Based on these results it can be concluded that the cooperative mathematics learning model based on blended learning to improve learning outcomes of class X MA students can be used practically.